SANKSI PIDANA TERHADAP PELAKU GRATIFIKASI SEKS - Azizah, Amirotul; Sandhi Sudarsana, I Ketut (Kertha Wicara : Journal Ilmu Hukum, 2013)
This paper entitled “Criminal Sanctions Against Sex Gratification Actors”. This paper uses the normative analytical method. Refers to the some cases of sexual gratification, is wasn’t easy to charge the doers with criminal sanction. That can be drawn from the issues, how the regulation of sex gratification in Indonesian criminal law, which is seen from the existing regulations there are still vacuum norm, and explains the criminal sanction that is applied to the doers of sex gratification that will provide a deterrent effect against doers. Sex gratification regulation perceived need specifically organize thoroughly and detailed as the existing regulations. Doers of sex gratification giver and receiver can be charged or indicted with the provisions of Act no. 20 Year 2001 on Eradication of Corruption, but the Act contains a provision not sanction against female doers of provider. Regulations with criminal sanction can be severe such as efforts to prevent of sex gratification, so the deterrent effect should be given to the doers of gratification in order not to repeat the offense again and prevent, which in this case in the form of criminal sanctions. The purpose of this writing is to analyze the regulation criminal law and sanction order to prevent the occurrence of Gratification Sex and contribute as well as discourse for legislators to establish a specifically for the regulation of Sex Gratification.
Keywords: Sex Gratification, Regulation, Criminal Sanction, Criminal Law